WOMEN LEADERS IN HIGH‐POVERTY COMMUNITY SCHOOLS: WORK‐RELATED STRESS AND FAMILY IMPACT - Lawson, Jennifer (Canadian Journal of Education/Revue canadienne de l’éducation, 2008)
This qualitative study explores the experiences of women administrators in high‐ poverty community schools, investigating four women’s perspectives on work demands and the impact on their families. Their work demands are related to the characteristics of impoverished communities, whereas their work resources are based on intrinsic rewards and social justice. Family demands and resources are related to the developmental stages of families, and therefore vary among the women inter‐ viewed. The research identifies the boundary‐spanning demands between work and home, and the resources and strategies used by these educational leaders to manage the challenges of working in high‐poverty community schools. Key words: school leadership, urban education, principals, inner‐city schools Cette étude qualitative porte sur les expériences de directrices d’école dans des milieux défavorisés. L’auteure analyse le point de vue de quatre femmes sur les exigences de leur travail et l’impact sur leurs familles. Les exigences de leur travail sont reliées aux caractéristiques des milieux pauvres tandis que leurs ressources professionnelles se fondent sur des récompenses intrinsèques et la justice sociale. Les exigences et les ressources en matière familiale sont liées au stade de développement des familles et varient donc d’une répondante à l’autre. La recherche identifie les exigences quant à l’interpénétration des frontières entre le travail et la maison ainsi que toutes les ressources et stratégies utilisées par ces cadres en vue de faire face aux défis de travailler au sein d’écoles implantées dans des milieux défavorisés. Mots clés : direction d’école, école urbaine, directeurs d’école, écoles dans des milieux défavorisés